If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(2v-5)+4v=4(v+3)
We move all terms to the left:
-2(2v-5)+4v-(4(v+3))=0
We add all the numbers together, and all the variables
4v-2(2v-5)-(4(v+3))=0
We multiply parentheses
4v-4v-(4(v+3))+10=0
We calculate terms in parentheses: -(4(v+3)), so:We add all the numbers together, and all the variables
4(v+3)
We multiply parentheses
4v+12
Back to the equation:
-(4v+12)
-(4v+12)+10=0
We get rid of parentheses
-4v-12+10=0
We add all the numbers together, and all the variables
-4v-2=0
We move all terms containing v to the left, all other terms to the right
-4v=2
v=2/-4
v=-1/2
| 15÷x=19 | | -21=-7w+3(w+5) | | 42=8x-14 | | 41=8x-14 | | -4(u+1)=3u+17 | | 3x+5-6=14 | | (5x+8)/(x-1)=6 | | 14-8x=42 | | -8w+4(w-5)=16 | | W=z+1 | | a+3/4=-1/4 | | 47=3v+8 | | S+4t= | | 0.4(f+9)=12 | | 4+n=3n | | 3z+18=2z/4 | | 2n+6=2(n+) | | 68=4x+8 | | x/7-4=-10 | | x+10+x+13=19 | | F=q+2 | | 3/4x(x+8)=9 | | 4x-3=2x/7+1 | | 4x-3=2x/7=1 | | -y^2-9y+15=29 | | 2x+3-4x-5=0 | | -x-2=9(2-3x)+6 | | -20-11c=2c+20-15c | | 3x-5=6x-65 | | p−1/4X3=−56 | | 125=-13x-122 | | 16t=4+17t |